Application of legumes in the formulation of gluten-free foods: functional, nutritional and nutraceutical importance - Imam, Yunus Temitayo; Irondi, Emmanuel Anyachukwu; Awoyale, Wasiu; Ajani, Emmanuel Oladipo; Alamu, Emmanuel Oladeji (Frontiers in Sustainable Food Systems, 2024)
This study presents a review of the application of legumes in the formulation of gluten-free foods (GFFs), with emphasis on their functional, nutritional, and nutraceutical importance. Consumption of GFF and abstinence from gluten-containing foods are the only options for managing celiac disease and gluten intolerance. Its formulation has also increased due to the increasing desire for healthy food by consumers. Recently, legume crops, such as Phaseolus vulgaris (bean), Brachystegia eurycoma (bean pod), Detarium microcarpum (sweet detar), Cetatonia siliqua (carob fruit), Cicer arietinum (chickpea), Pisum sativum (pea), Lens culinaris (lentil), and Vigna subterranean (Bambara nut) have been used in the production of GFFs. They belong to the family Leguminosae (Fabaceae), grown for their high protein content, and are the most important crop after cereals. Using legume flours as ingredients in GFFs formulation provides functional, nutritional, and nutraceutical benefits. They enhance the functional properties of GFFs, including volume, crumb, texture, and sensory qualities. They also improve the GFFs' nutritional properties, especially protein and dietary fiber, as well as their nutraceutical properties, such as laxative, anti-hyperglycemic, and antioxidant properties. Hence, adding legumes to GFF formulations might be a good way to enhance their functional, nutritional, and nutraceutical properties